2007
DOI: 10.1007/s00018-007-6447-x
|View full text |Cite
|
Sign up to set email alerts
|

Investigating metal-binding in proteins by nuclear magnetic resonance

Abstract: Metal ions play a key role for the function of many proteins. The interaction of the metal ion with the protein and its involvement in the function of the protein vary widely. In some proteins, the metal ion is bound tightly to the ligand residues and may be the key player in the function of the protein, as in the case of blue copper proteins. In other proteins, the metal ion is bound only temporarily and loosely to the protein, as in the case of some metalloenzymes and other proteins where the metal ion acts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 179 publications
0
37
0
Order By: Relevance
“…Most of the useful techniques require pure sample for analysis such as Xray crystallography, nuclear magnetic resonance (NMR), Fourier transform infra-red spectroscopy (FTIR), circular dichroism (CD) spectroscopy, surface plasmon resonance (SPR) and atomic force microscopy (AFM) [9,10]. NMR technique performs with highly concentrated samples, and is restricted for small and soluble proteins (<40 kDa) due to often observed spectral overlaps for large proteins [11]. The preparation of biological crystal for X-ray crystallography is predominately difficult and in some cases impossible [9].…”
Section: Analytical Techniques For Studying Protein-metal Interactionsmentioning
confidence: 99%
“…Most of the useful techniques require pure sample for analysis such as Xray crystallography, nuclear magnetic resonance (NMR), Fourier transform infra-red spectroscopy (FTIR), circular dichroism (CD) spectroscopy, surface plasmon resonance (SPR) and atomic force microscopy (AFM) [9,10]. NMR technique performs with highly concentrated samples, and is restricted for small and soluble proteins (<40 kDa) due to often observed spectral overlaps for large proteins [11]. The preparation of biological crystal for X-ray crystallography is predominately difficult and in some cases impossible [9].…”
Section: Analytical Techniques For Studying Protein-metal Interactionsmentioning
confidence: 99%
“…This is mainly because of the chemical versatility of its imidazole ring, which includes two neutral, chemically distinct forms, and a protonated form, referred to as N δ1 -H and N ϵ2 -H tautomers, and H þ , respectively, with one form favored over the other by the protein environment and pH. Moreover, His with a pK°of 6.6 (2) titrates around neutral pH, allowing the deprotonated nitrogen of its imidazole ring to serve as an effective ligand for metal binding (3). In particular, it has been suggested that tautomerization and variations of χ1 of His are crucial parts of the proton-transfer process (4).…”
mentioning
confidence: 99%
“…However, since the 1990s techniques have been developed to use the paramagnetic cofactor to retrieve structural restraints to solve metal binding site structures. Some excellent reviews are available explaining how to use a paramagnetic cofactor to deliver structural restraints [14,17,[112][113][114][115].…”
Section: Structure Determination Of Paramagnetic Proteinsmentioning
confidence: 99%